The significance of G/C polymorphism of the RAD51 gene in postmenopausal women with breast cancer - Romanowicz-Makowska, Hanna; Smolarz, Beata; Sobczuk, Anna; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Objective: Breast cancer is one of the major killers worldwide. In this study the G/C polymorphism of the RAD51 gene in women with breast cancer was investigated. Material and methods: 100 breast cancer women provided blood for mutation analysis. Blood samples from age-matched healthy individuals (n=106) served as controls. The G/C polymorphism was determined by PCR-RFLP methods. Results: The distribution of genotypes of the G/C polymorphism of RAD51 in both controls and patients did not differ significantly (p>0.05) from those predicted by the Hardy-Weinberg distribution. There were no significant differences in the genotype distributions and allele frequencies between node-positive and node-negative patients. Conclusion: Our study implies that it is possible that the G/C polymorphism of the RAD51 gene may not be directly involved in the development and/or progression of breast cancer, but further research, conducted on a larger population, is needed to clarify this point.